The Influence Social Support on Self-Efficacy and Quality of Life in Breast Cancer Patients - Farhan, Ulfa Fadhila; Nursal, Dien Gusta Anggraini; Semiarty, Rima (Newinera Publisher, 2025)
The world-wide morbidity and mortality statistics indicate breast cancer holds its position as one of the leading diseases which affects patient psychology and social life in addition to causing physical harm. The medical interventions for disease control meet limited needs because patients' quality of life during and following chemotherapy strongly depends on their psychosocial factors especially social support and self-efficacy. The research analyzed how social support affects self-efficacy and quality of life in breast cancer patients receiving chemotherapy through self-efficacy as a possible mediator. The research design involved 95 breast cancer patients enrolled in chemotherapy treatment at Dr. M. Djamil Padang General Hospital. Consecutive sampling was used. The research data collection involved structured questionnaires followed by a Statistical Equation Modeling analysis through SmartPLS 4.0. Research examined direct along with indirect consequences through analyses which measured model explanatory capability. The research showed a strong positive link between social support leading patients to enhance self-efficacy (path coefficient = 0.922; p < 0.001) while still showing a moderate positive relation toward quality of life (path coefficient = 0.505; p < 0.001). The influence of self-efficacy on quality of life reached 0.499 significance (p < 0.001) with social support acting as a mediating factor (indirect effect = 0.460; p < 0.001). The research model established that psychosocial variables explained 85% and 80.5% of variance in patient outcomes for self-efficacy and quality of life respectively.